Frequency and significance of HIV infection among patients diagnosed with thrombotic thrombocytopenic purpura - Benjamin, Melody; Terrell, Deirdra R; Vesely, Sara K; Voskuhl, Gene W; Dezube, Bruce J; Kremer Hovinga, Johanna A; Lämmle, Bernhard; George, James N (Clinical infectious diseases, 2009)
Case series of patients with a diagnosis of thrombotic thrombocytopenic purpura (TTP) have reported different frequencies of human immunodeficiency virus (HIV) infection; some series suggest that HIV infection may cause TTP. We systematically reviewed all reports of HIV infection in case series of patients with TTP. We analyzed data from the Oklahoma TTP-HUS (hemolytic uremic syndrome) Registry, an inception cohort of 362 consecutive patients, for 1989-2007. Nineteen case series reported the occurrence of HIV infection at the time of diagnosis of TTP in 0%-83% of patients; individual patient data were rarely described. The Oklahoma TTP-HUS Registry determined the HIV status at the time of diagnosis of TTP in 351 (97%) of 362 patients. HIV infection was documented in 6 (1.84%; 95% CI, 0.68%-4.01%) of 326 adult patients (age, 26-51 years); follow-up data were complete for all 6 patients. The period prevalence of HIV infection among all adults in the Oklahoma TTP-HUS Registry region for 1989-2007 was 0.30%. One patient had typical features of TTP with 5 relapses. Five patients had single episodes; in 4, the clinical features that had initially suggested the diagnosis of TTP were subsequently attributed to malignant hypertension (in 3 patients) and disseminated Kaposi sarcoma (in 1 patient). HIV infection, similar to other inflammatory conditions, may trigger acute episodes of TTP in susceptible patients. More commonly, acquired immunodeficiency syndrome-related disorders may mimic the clinical features of TTP. If the diagnosis of TTP is suggested in a patient with HIV infection, there should be careful evaluation for alternative diagnoses and cautious consideration of plasma exchange, the required treatment for TTP.